The influence of L1 on the acquisition of stress and intonation patterns of English: a case in the United States - Sefain, Samir (Erudita: Journal of English Language Teaching, 2025)
Most ESL learners have a foreign accent in their speech owing to the significant influence of their mother tongue on their production of English pronunciation. Most previous literature has stressed the segmental area that focuses on single sounds and provided an accurate list of the tricky vowels, along with the level of difficulty to be avoided. This research aimed to measure the level of awareness of teachers and learners regarding the topic, both qualitatively and quantitatively, and presented some efficient methods for presenting intonation, stress, and rhythm patterns. Additionally, the study examined the role of the curriculum in guiding the learning process and the impact of exposing learners to native speakers in defining certain variables. To collect the data, the researcher used interviews, observation, and questionnaires. There were 15 non-native and TESL Ontario-licensed teachers participating in this study, who were interviewed. The study found a significant link between the teachers’ degrees and experience and the level of awareness, tolerance to the learners’ mistakes in this area, and the curriculum focus. This study contributes to the understanding that exposing ESL learners to native speakers’ accents can help facilitate the concept of acculturation and prevent diglossia in the English language learning process.